RELATIONSHIP WORK DISCIPLINE WITH JOB SATISFACTION OF NURSES IN HOSPITAL ISLAM KHASANAH MUHAMADIYAH MOJOKERTO - Sulis Fitri Qodariyah; Arif Wijaya; Yunan Yusuf Habibi (Jurnal Keperawatan, 2014)
Discipline is the key to achieving the goal of an organization, so the discipline of work must be considered by the organization. There are several things that can affect labor discipline, one of which is job satisfaction. The purpose of this study to determine the relationship between work discipline with the level of job satisfaction of nurses in Hospital Islam Khasanah Muhamadiyah Mojokerto. The design of this study used an observational study conducted by cross sectional analytical cross sectional. This study was conducted in Hospital Islam Khasanah Muhamadiyah Mojokerto, total sampling method with a sample of 55 nurses. Data collection using questionnaires. Analysis of the data using statistical test product moment correlation. The results showed that there was a relationship work discipline and job satisfaction of nurses in Hospital Islam Khasanah Muhamadiyah Mojokerto. with probability value as 0,001 more than value α (0,05), in order to H1 accepted. Working discipline have average 10.45, minimum 6 and maximum 14 and dan working satisfaction have average 44.04, minimum 20 and maximum 58. Work discipline has a relationship with job satisfaction of nurses in hospital Islam Khasanah Muhamadiyah Mojokerto. Sugestion to hospital Islam Khasanah Muhamadiyah Mojokerto expected satisfaction of nurses in the work needs to be understood by the agency as the greatest asset in the development of services that are more specific and comprehensive, thus increasing profits for a hospital that supports the increasing moral and material fulfillment for nurses who improve nurse satisfaction in work.Keyword : Working dicipline, Satisfaction